Beyond the pandemic: A cross-sectional study of haematology cancer patients' unmet needs and experiences of cancer care in Ireland and the UK - Boland, Vanessa; Drury, Amanda (My University, 2025)
Objectives: The rising incidence of hematological cancers, novel treatments, and increased survivorship highlight the need to understand patient needs postpandemic. This study explored the experiences of individuals affected by hematological cancers in Ireland and the UK as COVID-19 restrictions lifted. Methods: A cross-sectional descriptive survey was conducted from March 2023 to March 2024 using validated measures of distress, resilience, and unmet needs. Adults with hematological cancers were recruited online through cancer organizations and networks across Ireland and the UK. Quantitative data were analyzed using descriptive and inferential statistics, and qualitative data through thematic analysis. Results: Ninety-two individuals completed the survey. The top unmet needs were related to tiredness, concerns about appearance, and managing others’ expectations to return to “normal.” Many continued to feel the pandemic’s impact years later. Minimal differences in unmet needs were observed between countries, with participants reporting low distress and moderately high resilience. Thematic analysis of text responses identified three key themes: “psychological impact and self-care methods,” “navigating changing cancer care delivery,” and “sourcing social support,” reflecting the complexities of living with and beyond hematological cancers. Conclusions: People with hematological cancers in Ireland and the UK continue to experience distress despite moderate resilience, indicating the lasting impact of the pandemic. Implications for Nursing Practice: Persistent unmet needs around fatigue, appearance, and societal expectations remain. The identified themes underscore the need for supportive interventions focusing on psychological coping strategies, continuity in cancer care delivery, and social support to enhance the well-being of individuals living with and beyond hematological cancers.
PUBLISHED
Keywords: Blood cancers; Hematological malignancies; Leukaemia; Lymphoma; Myeloma; Cancer; Cancer Survivorship; blood cancer; unmet needs